On commerce and usury (1524) - Luther, Martin, 1483-1546 (Economic ideas that build Europe., 2015)
This volume presents Martin Luther's contribution to the modern economic sciences, providing a detailed introduction and revised translation of his 1524 pamphlet, 'On Commerce and Usury' ('Von Kauffshandlung vnd Wucher').